Digger and Tom! - Braun, Sébastien (Harper / HarperCollins, 2013)
The building site will not be ready until one last rock is removed, and although the big machines all have a go at it, only Little Digger has what it takes to get the job done...with some encouragement from Tom, the dump truck
Keywords: Construction equipment; Determination (Personality trait); Kinderbuch